Peran Inovasi (PETIK DUREN) Pelayanan Tilik Kampung Penduduk Rentan dalam Meningkatkan Kesejahteraan Masyarakat Kabupaten Lamongan - Rosalina Ikawati; Ika Devy Pramudiana; Widyawati Widyawati; Sri Roekminiati (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
PETIK DUREN Program (Pelayanan Tilik Kampung Penduduk Rentan) is a public service innovation in Lamongan Regency aimed at improving access to civil administration for vulnerable groups, such as individuals with mental health disorders (ODGJ) and persons with disabilities. This study analyzes the program's success using Everett M. Rogers' diffusion of innovation theory, which includes indicators of relative advantage, compatibility, complexity, trialability, and observability. Using a descriptive qualitative method with a case study approach, data were collected through in-depth interviews and official government reports.The analysis results show that the program successfully registered 161 individuals in 2023 and an additional 16 individuals by May 2024. Success is evident in the trialability and observability aspects, demonstrated through improved access to healthcare, education, and social assistance services. Simplified procedures and a proactive approach facilitate vulnerable groups in accessing civil documents. The program meets innovation indicators, especially relative advantage and compatibility, by creating efficient services tailored to local needs.However, challenges such as low community participation in certain areas and logistical constraints remain. Recommendations include strengthening data verification technology, training officers, and implementing a zoning approach to expand coverage. With these improvements, PETIK DUREN has the potential to become a national model for public service innovation in improving the welfare of vulnerable communities.